Performance optimization in Danish elite badminton - Strength and conditioning - Brink Hansen, M. (2018 Sports Science Conference, Halmstad University 25th-27th April 2018, 2018)
During the 2018 Sports Science Conference, staged at the Halmstad University from the 25th to the 27th of April, just before the Liebherr 2018 World Team Championships, Mads Brink Hansen gave an interesting lecture about performance optimization in Danish Badminton with a focus on strength and conditioning.